2019
DOI: 10.3390/en12234513
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Evolution Law of Overburden Breaking Angle under Repeated Mining and the Application of Roof Pressure Relief

Abstract: Aiming at the serious problems caused by coal mine mining activities causing the rock burst accidents, this paper is based on rock mechanics and material mechanics to establish the key layer breaking by the double-key layer beam breaking structural mechanics model of a single working face and double working face under repeated mining. The theoretical calculation formula of the angle was used as the theoretical basis for the elevation angle of the pre-reloading hole of the hard roof. The rationality and reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Bolts are vital to the advancement of underground excavation in engineering work, such as subway tunnels and coal mines, as they connect broken rock mass, enhance the stability of underground coal mine roadways and surrounding rock, and reduce the occurrence of rock burst . In countries such as China where huge amount of coal is mined, problems of roof falling (roof collapse), land subsidence, and collapse result in a series of secondary disasters, directly threatening production, and life safety . Monitoring and evaluation of the anchoring performance is an important basis to judge the effectiveness of bolts, and hence, to ascertain the safety of the underground coal mine roadways.…”
Section: Introductionmentioning
confidence: 99%
“…Bolts are vital to the advancement of underground excavation in engineering work, such as subway tunnels and coal mines, as they connect broken rock mass, enhance the stability of underground coal mine roadways and surrounding rock, and reduce the occurrence of rock burst . In countries such as China where huge amount of coal is mined, problems of roof falling (roof collapse), land subsidence, and collapse result in a series of secondary disasters, directly threatening production, and life safety . Monitoring and evaluation of the anchoring performance is an important basis to judge the effectiveness of bolts, and hence, to ascertain the safety of the underground coal mine roadways.…”
Section: Introductionmentioning
confidence: 99%
“…Parameters c ε and r ε are the strain at the peak point and ultimate failure point. From Equations (1) and (5), it can be found that both of the indexes et W and e K can determine energy accumulating and releasing ability of coal. For the index K e , which is defined as the ratio of accumulated strain energy density before the peak strength u a to the released strain energy density after peak strength u r , can be calculated with uniaxial compression test.…”
Section: Burst Proneness None Low Highmentioning
confidence: 99%
“…Parameters c ε and r ε are the strain at the peak point and ultimate failure point. From Equations (1) and (5), it can be found that both of the indexes et W and e K can determine energy accumulating and releasing ability of coal. Similarly, the parameters u a and u r can be expressed by following equations:…”
Section: Burst Proneness None Low Highmentioning
confidence: 99%
See 1 more Smart Citation
“…We define the phenomenon of rock burst induced by the unilateral or comprehensive influence of the stope advancing speed and stopping time as the advancing speed-stoping time effect. In this paper, we deduce the theoretical calculation formula of the key stratum fracture angle and study the fracture situation of the key stratum of the overburden in the mining process of the working face [25]. Then, the method of combining microseismic monitoring technology with similar simulation experiments is used, and only the influence of the advancing speed-stoping time effect on the characteristics of microseismic events is considered, thus revealing the mechanism of rock burst induced by the advancing speed-stoping time effect of the working face.…”
Section: Introductionmentioning
confidence: 99%